A Critical Analysis of Class X English and Social Science Question Papers - Chandrasekha, K. (INDIAN EDUCATIONAL REVIEW, 2007)
Examinations play a very important role in Indian system of education. They are so important that they direct the entire teaching learning process in schools. These examinations use mainly one tool to evaluate the achievement of the students and that is the ‘question paper’. So, if the public examinations have to stay till a viable mechanism of evaluation comes into effect, question papers used by the State Boards of Education in their public examinations need to be continuously examined and improved specially for the purpose of improving the quality of education at school stage. It was in this backdrop that a study of Class X English and Social Science Question Papers of Punjab School Education Board was undertaken. The objective of the study was to find out whether the question papers are valid and reliable and whether they fulfill the criteria of balanced question papers and what were their strengths and weaknesses.